ON THE MEANING OF JOB 26:9 - Pinker, Aron (Journal for Semitics, 2017)
This study suggests that the difficulties in understanding Job 26:9 in context stem from a transcriberâ€™s erroneous transposition of the two words ×›×¡×” and ×¤×¨×©×– . It is argued that the original reading was ×žÖ°×Ö·×—Öµ×– ×¤Ö° × Öµ×™ ×¤Ö·×¨Ö¾Ö¾×¢×•Ö¹×– ×›Ö¼Ö´ ×¡×” ×¢ ×œ×™×• ×¢Ö²×  × ×•Ö¹ , â€œHe holds the face of a mighty ox, His cloud covers himâ€. This can be paraphrased: â€œGod puts a constraint on the face of the mighty bull (Behemot) and covers him with His cloud so that he would not be affected by the drying sunâ€. The verse does not admit a celestial or cosmographic interpretation, but a mythological understanding. It depicts typical divine behaviour, which exhibits control and concern. Mentioning Behemot in v. 9 complements the reference to the sea monsters (×¨×”×‘ and × ×—×© ×‘×¨×™×— ) in the following verses with a land monster.